Perbandingan Konsep Manajemen Ekonomi Konvesional Dan Ekonomi Islam - Adellia; Dewi Sartika; Yuheldi Pebriansyah Putra; Nelsa Agustin (ICONS: Islamic Economics Journal, 2025)
Islamic Economics is an economy based on divinity. There is a fundamental difference in paradigm between Islamic Economics and conventional economics. Economics that views conventional science as something secular while Islamic Economics is built on religious principles. The Islamic Economic System distinguishes between economic discussions from the perspective of production of goods and services covered in economic discussions" and economic discussions from the perspective of how to obtain, to use, and to distribute goods and services covered in economic system discussions". The conventional economic system makes economic discussions" and "economic systems" as an inseparable unity.